Protein Kinase Cα Modulates Estrogen-Receptor-Dependent Transcription and Proliferation in Endometrial Cancer Cells - Alicia M. Thorne; Twila A. Jackson; Van C. Willis; Andrew P. Bradford (Obstetrics and Gynecology International)
Endometrial cancer is the most common invasive gynecologic malignancy in developed countries. The most prevalent endometrioid tumors are linked to excessive estrogen exposure and hyperplasia. However, molecular mechanisms and signaling pathways underlying their etiology and pathophysiology remain poorly understood. We have shown that protein kinase Cα (PKCα) is aberrantly expressed in endometrioid tumors and is an important mediator of endometrial cancer cell survival, proliferation, and invasion. In this study, we demonstrate that expression of active, myristoylated PKCα conferred ligand-independent activation of estrogen-receptor- (ER-) dependent promoters and enhanced responses to estrogen. Conversely, knockdown of PKCα reduced ER-dependent gene expression and inhibited estrogen-induced proliferation of endometrial cancer cells. The ability of PKCα to potentiate estrogen activation of ER-dependent transcription was attenuated by inhibitors of phosphoinositide 3-kinase (PI3K) and Akt. Evidence suggests that PKCα and estrogen signal transduction pathways functionally interact, to modulate ER-dependent growth and transcription. Thus, PKCα signaling, via PI3K/Akt, may be a critical element of the hyperestrogenic environment and activation of ER that is thought to underlie the development of estrogen-dependent endometrial hyperplasia and malignancy. PKCα-dependent pathways may provide much needed prognostic markers of aggressive disease and novel therapeutic targets in ER positive tumors.